PENGEMBANGAN BUDAYA BACA DI KOMUNITAS ADAT (PENYELENGGARAAN TBM DI KOMUNITAS ADAT SAMIN) - Purbaningrum, Febri Hartanti; Djumadi, Djumadi (JIV-Jurnal Ilmiah Visi, 2017)
Samin indigenous community is a group of Saminist adherent located in Blora District. Government, with one of its programs—literacy movement, found obstacles in this community which is very closed and careful in accepting new things out of the community. This research aims to get reading culture development, recognize the feasibility and effectiveness of reading culture development model in that community. The model uses a research and development (R&D) approach which is an improvement method developed by Borg and Gall. Methods used are descriptive and qualitative. This research was conducted in Samin community, Sambongrejo village, Kecamatan Sambong Blora District, starting from July to November 2016. Results of this research has been appropriate to the effectiveness test conducted, so that it can be revealed that this model is effective and feasible to be examined extensively to an indigenous community. This research also gives suggestions on how to overcome problems in which the management of community Reading Garden has to do strategic steps so that TBM can be managed well in the planning, execution, and service process.